Peningkatan Kompetensi Mata Pelajaran Matematika dengan Materi Pola Barisan dan Deret Menggunakan Model Discovery Learning Pada Siswa Kelas XI IIS 1 di MAN 1 Banjarmasin Tahun Pelajaran 2016/2017 - Yusfita kumala dewi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2018)
Discovery learning is a teaching method that emphasizes the importance of helping students to understand the structure or key ideas of a discipline. The purpose of this study is to know the use of discovery learning method in improving students' competencies cognitive and affective aspects in understanding the material Pattern Barisan and Series in class XI IIS 1 MAN 1 Banjarmasin Year 2016/2017. The type of research is Classroom Action Research (PTK). Consisting of 2 Cycles that each cycle in this study was held for 3 meetings. The study was conducted in class XI IIS 1 MAN 1 Banjarmasin in January-April 2017 with a population of 35 students. Data analysis in this classroom action research is done through the first three stages of data reduction, the two describe the data and the three make a conclusion. The average value of the class has increased from 76.43 in the first cycle to 80.57 in postes cycle II. While the percentage of classical completeness rose by 67.24% in the first cycle to 85.71% in cycle II. The affective aspect is increased from cycle I to cycle II. In the first cycle of affective percentage of 71.43% categorized Enough whereas in cycle II there is not enough categorized and in cycle I good category of 28.57% rose to 100% categorized well on cycle II.